Nierolniczy sektor prywatny gospodarki w polityce ekonomicznej władz komunistycznych po 1980 roku - Kaliński, Janusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
In the early 1980s, following the rapidly growing economic imbalance, substantial foreign debt, and the strength of social protest in the summer of 1980, communist authorities in Poland started working on structural changes in the planned economy. As the decision-makers emphasized, the proposed reforms would not undermine the principles of the state’s political and governmental system; the assent to the limited development of the non-agricultural private sector stemmed from believing in its beneficial influence on the victualing of the population. At the beginning of the 1980s, certain legal conditions were introduced to enable the creation of hybrid enterprises with the participation of foreign economic entities and enterprises belonging to foreign natural and legal persons. More extensive opportunities for the development of domestic and foreign entrepreneurship appeared in 1988 with the passing of the Act on Economic Activity and the Act on Economic Activity with the Participation of Foreign Parties. Facilitating the development of the private small-business sector did not coincide with an intent to privatize state-owned enterprises. What it indicated was a desire to create, in the fashion of the Soviet perestroika, a hybrid economic system, one generating numer-ous pathologies. Compared to the so-called socialized sector, the dynamics of private companies were higher, according to official statistics. As a result, there was a limited increase in the GDP contribution of private ownership. However, the non-agricultural private sector worked under conditions of strong dependence on state-owned and pseudo-cooperative enterprises that dominated the economy.